Does Transfer Motivation Succeed in Mediating in the Context of Training Transfer? - Dida Sovia Wirdani; Nury Ariani Wulansari (Faculty of Economic and Business, 2019)
The purpose of this study is to examine and find out the mediating effect of transfer motivation on the relationship between supervisor support and peer support on training transfers in Kantor Pelayanan Pajak (KPP) Pratama Semarang Timur and Selatan employees. This study took a sample of 130 employees by using proportional random sampling technique. The data collection method was carried out by means of a survey, namely interviews and questionnaires. The data analysis method uses descriptive statistical tests and partial least square. The results of this study were accepted both direct and indirect effects (mediation). The conclusion of this study is that KPP Pratama Semarang Timur and Selatan employees must improve the implementation of training results to work and believe that the successful implementation of knowledge, attitude skills can improve their performance.